2005
DOI: 10.1088/1126-6708/2005/05/070
|View full text |Cite
|
Sign up to set email alerts
|

Center vortices and the Gribov horizon

Abstract: We show how the infinite color-Coulomb energy of color-charged states is related to enhanced density of near-zero modes of the Faddeev-Popov operator, and calculate this density numerically for both pure Yang-Mills and gauge-Higgs systems at zero temperature, and for pure gauge theory in the deconfined phase. We find that the enhancement of the eigenvalue density is tied to the presence of percolating center vortex configurations, and that this property disappears when center vortices are either removed from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
154
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(170 citation statements)
references
References 29 publications
15
154
1
Order By: Relevance
“…(i) The massive level crossing makes the density of states, that is, the density of zero-modes, of the operator M diverge as compared to the density of zero modes of the Laplacian operator. This fits nicely with confinement scenario described in [20][21][22] where the divergence of the CCP is also understood as resulting from an enhanced density of states.…”
Section: Zero Modes Of Faddeev-popov Operator and Confinementsupporting
confidence: 86%
“…(i) The massive level crossing makes the density of states, that is, the density of zero-modes, of the operator M diverge as compared to the density of zero modes of the Laplacian operator. This fits nicely with confinement scenario described in [20][21][22] where the divergence of the CCP is also understood as resulting from an enhanced density of states.…”
Section: Zero Modes Of Faddeev-popov Operator and Confinementsupporting
confidence: 86%
“…In particular, the confining two point function is thought be due to a non-perturbative enhancement in the density of near-zero eigenvalues of the Faddeev-Popov operator, associated with the proximity of typical vacuum configurations to the Gribov horizon. It has been shown via lattice Monte Carlo simulations that removal of center vortices from thermalized lattice configurations sends this eigenvalue density back to the perturbative form [24], and the corresponding Coulomb string tension (along with the asymptotic string tension) vanishes upon vortex removal [10] (for recent developments in the vortex picture, see [25]). If center vortices or some other topological objects are responsible for the linearly rising Coulomb potential, it is probably necessary to also appeal to a topological mechanism in order to understand the formation of a Coulomb flux tube.…”
Section: Discussionmentioning
confidence: 99%
“…A central element of the Gribov-Zwanziger confinement scenario in Coulomb gauge is the instantaneous colorCoulomb potential involving the Faddeev-Popov operator M (in Coulomb gauge) and the infrared spectral properties of the latter [5,6]. The expression V Coul ðx À yÞ ab ¼ hg 2 ½M À1 ðÀ4ÞM À1 ab ðx; yÞi…”
Section: Introductionmentioning
confidence: 99%
“…Recent lattice studies have shown, however, that the relation (4) is only a necessary [9] condition for confinement, and that the Coulomb potential can be linearly rising with spatial distance even in the deconfinement phase [6,10]. Using lattice techniques, a linearly rising Coulomb potential [9][10][11] and a connection between the center-vortex mechanism and the Gribov-Zwanziger scenario [5,12,13] have been observed. Furthermore, Greensite et al proposed [14] to use correlators of partial Polyakov loops to measure the Coulomb potential.…”
Section: Introductionmentioning
confidence: 99%